1996
DOI: 10.1177/108835769601100302
|View full text |Cite
|
Sign up to set email alerts
|

Using Anchored Instruction to Teach About Assistive Technology

Abstract: This investigation reports about the development and formative evaluation of an assistive technology instructional module that was developed in an integrated hypermedia format according to principles of anchored instruction. The module was field-tested with undergraduate students, graduate students, and professionals. Revisions were made in the module on the basis of feedback from the field tests. It was concluded that people respond positively to anchored instruction on the topic of assistive technology and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Anchored instruction method has been used with positive results to promote content understanding in social studies (Glaser, Rieth, Kinzer, Prestidge & Peter, 1999;Okolo, Ferretti & MacArthur, 2002) and English language arts (Rieth et al, 2003) and to develop proficiency with mathematics (Bottge, Heinrichs, Chan, Mehta & Watson, 2003).The concept has been used to examine gains in achievement in mathematics for students in general (Shyu, 2000) and teaching students and professionals about assistive technology (Blackhurst & Morse, 1996). In the studies where the anchored instruction method is applied on fifth and sixth grade students, it is observed that their academic success improved in terms of their mathematics classes.…”
Section: Introductionmentioning
confidence: 99%
“…Anchored instruction method has been used with positive results to promote content understanding in social studies (Glaser, Rieth, Kinzer, Prestidge & Peter, 1999;Okolo, Ferretti & MacArthur, 2002) and English language arts (Rieth et al, 2003) and to develop proficiency with mathematics (Bottge, Heinrichs, Chan, Mehta & Watson, 2003).The concept has been used to examine gains in achievement in mathematics for students in general (Shyu, 2000) and teaching students and professionals about assistive technology (Blackhurst & Morse, 1996). In the studies where the anchored instruction method is applied on fifth and sixth grade students, it is observed that their academic success improved in terms of their mathematics classes.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of this literature review, only a few articles were found that described instructional methods or models for integrating assistive technology into teacher preparation programs (Anderson & Petch-Hogan, 2001;Blackhurst & Morse, 1996;Bryant, Erin, Lock, Allan, & Resta, 1998;Jeffs & Banister, 2006;Wojcik et al, 2004). Some researchers described instructional methods for integrating assistive technology into teacher education programs.…”
mentioning
confidence: 99%
“…Some researchers described instructional methods for integrating assistive technology into teacher education programs. For example, Blackhurst and Morse (1996) described the development and pilot use of a module on AT developed using hypermedia that followed principles of anchored instruction. The module incorporated videos and other multimedia and was used and evaluated by three different groups (undergraduate students, graduate students, and inservice professionals).…”
mentioning
confidence: 99%
“…In teacher education, the intent is to ease the transition from preservice teacher to successful induction. MAI has been used to deliver content in both general education and special education teacher education (Blackhurst & Morse, 1996;Kumar & Sherwood, 1997;Langone, Malone, Stecker, & Greene, 1998;Welch & Brownell, 2002). In light of the proliferation of technology in teacher education and the widespread use of video as an instructional medium, a synthesis of the literature on MAI to summarize findings, discuss implications for future research, and develop recommendations for current practice would be useful.…”
Section: Multimedia Anchored Instructionmentioning
confidence: 99%